Efficacy and safety of broad spectrum penicillin with or without beta-lactamase inhibitors vs first and second generation cephalosporins as prophylactic antibiotics during cesarean section: a systematic review and meta-analysis - Qianqian Song; Jingjing Yan; Na Bu; Ying Qian (Taylor & Francis Group, 2023)
This study assessed the efficacy and safety between broad spectrum penicillin (P2) with or without beta-lactamase inhibitors (P2+) versus first and second generation cephalosporins (C1&C2) in the prevention of post-cesarean infections. Relevant randomized controlled trials (RCTs) were searched in English and Chinese databases: nine RCTs were involved. Six trials compared P2+ vs C1&C2, no differences were found between interventions for endometritis, wound infection, urinary tract infection, febrile morbidity and maternal rashes. Four trials compared P2 vs C1&C2, no differences were found between interventions for endometritis, febrile morbidity, wound infection and urinary tract infection. Postoperative hospitalization was longer for women in P2 than C1&C2. Based on these results, P2/P2+ and C1&C2 may have similar efficacy on postoperative infections after cesarean section, there is no data on infant outcomes. PROSPERO Registration Number: CRD42022345721.